Child-Teacher Relationship and Harmonious Interaction - Ode Yahyu Herliany Yusuf; Sumarzawan Sumarzawan; Wa Ode Arnam Mustika; Endang Lestari; Desi Ratna Sari; Acani Wali; Silviani Silviani; Suryati Suryati; Rohani Rohani; Hastati Hastati (CV. Rayyan Dwi Bharata, 2023)
Interaction in everyday life is a need that needs to be fulfilled by humans so that good interaction can have a good impact and a sense of comfort and security in establishing social life. while according to (Chaplin, 2011). Interaction is a social relationship between individuals in such a way that the individuals concerned influence each other. Where in reality that the relationship between interactions that occur between teachers and students can produce good or bad impacts on the effectiveness of children's learning. As is happening in Indonesian society today, there are many things that are related to the lack of harmonious relationships between teachers and students that cause inhibition in the teaching process in the school environment. Therefore, discussions were held between students about how to establish a harmonious relationship between teachers and students so as to have a positive impact.